Fast 128-bit Multi-Pass Stream Ciphering Method - Abdul-Jabbar, Safa S.; Abed, Abeer E.; Mohammed, Sajaa G.; Mohammed, Faisel G. (Iraqi Journal of Science, 2023)
Information is an essential and valuable object in all systems. The more information you have about your issue, the better you can conform to the world around you. Moreover, information recognizes companies and provides influence that helps one company be more effective than another. So, protecting this information using better security controls and providing a high level of access to authorized parties becomes an urgent need. As a result, many algorithms and encryption techniques have been developed to provide a high level of protection for system information. Therefore, this paper presents an enhancement to the Blowfish algorithm as one of the cryptography techniques. Then it proposes an enhancement for increasing efficiency and secrecy for this algorithm, which are the main criteria for these modifications. In this paper, the main modification made for the Blowfish algorithm is altering the S-box according to the principles of the block cipher (OFB). The results were approved using hamming distance and avalanche effect. The proposed algorithm presents advantages on several points, including reducing the required time for the encryption and decryption processes and preventing transmission errors from perpetuating all data. Also, we can conclude that the modified Blowfish algorithm can be used for all text encryption systems because of its flexibility (unlimited input text size and expanding key size).